Structural and Magnetic Properties of Fe3O4 Doped Zirconia. (2015) - Bashir, Mahwish; Riaz, Saira; Farooq, Muhammad; Butt, Anum; Naseem, Shahzad
Abstract: ZrO2 is one of the most well studied ceramic materials in biological field because of the excellent mechanical properties (strength and high fracture toughness, hardness) and biocompatibility. In this study magnetite (Fe3 O4 ) has been added into zirconia to stabilize it at room temperature. Different samples were prepared by varying iron oxide (Fe3 O4 ) concentrations by 0-10wt%. Sols of Fe3 O4 doped ZrO2 were spun on glass substrate at 3000 rpm for 30 seconds and annealed at 300 °C for 1 h. X-ray diffraction results confirm the formation of single phase ZrO2 for 8 and 10wt% of Fe3 O4 . However, low intensity peak of Fe3 O4 along with pure phase of tetragonal zirconia is observed for 10 wt% of Fe3 O4 concentration. Effect of reaction temperature (100 to 250 °C) on Fe3 O4 doped zirconia has also been studied for 6wt% of Fe3 O4 . X-ray diffraction results describe the formation of mixed phases at relatively low reaction temperature (100 °C), whereas with the increase in reaction temperature pure tetragonal zirconia (t-ZrO2 ) content increases. Relatively lower dislocation lines/m 2 has been observed at 200 °C reaction temperature along with pure tetragonal zirconia phase. Ferromagnetic behavior has been observed in Fe3 O4 doped zirconia with low value of coercivity (∼245 Oe) for all dopant concentrations. M-H curves reveal the formation of ferromagnetic behavior with low value of coercivity at temperature of 100 and 200°C.